(Re) atando políticas: sociedade, Estado e cinema no Brasil - Estevinho, Telmo Antonio Dinelli (2014)
This work aim is to make an analysis of Film Industry Policies in Brazil from the 1960s to the late 1990s. In this period, the main state agencies to support the Brazilian movie production were created and this specific policy remained basically constant regardless of political and economic changes in the country. For this, we use the concepts of historical institutionalism to demonstrate the resilience of a specific system in these policies and to explain the mechanisms that allowed its deployment over time. The centralization of the movie production unlinked to its public distribution, and the implementation of these policies by the educational and cultural state agencies were constant during more than 30 years what enabled interactions between the state and influent political sectors of Brazilian Film industry. This shows the influence of formal and informal Brazilian institutions over the public policy design and its respective implementation process. National agencies like Instituto Nacional de Cinema and Embrafilme were important because they meant to be an opened space in the state in order to make possible the interactions among filmmakers, producers and politicians. The cultural characteristics of the brazilian movies were also used for the maintenance and reproduction of these interactions. The research used a systematic analysis of the film legislation, studies and reports produced by professional associations and government institutes as well as interviews with Brazilian filmmakers, producers and politicians